Analisis Faktor yang Berhubungan dengan Perdarahan Postpartum RSUD Banten Tahun 2019-2023 - Trasia, Reqgi First; Anggraeni, Inggrid Dwi; Putra, Novitrian Eka (Penerbit Goodwood, 2025)
Purpose: This study aimed to analyze the factors associated with postpartum hemorrhage (PPH) among postpartum mothers at RSUD Banten from 2019 to 2023, focusing on both causal and predisposing factors.. Methodology/approach: An observational analytic study with a cross-sectional and retrospective design was conducted using secondary data from medical records in the Obstetrics and Gynecology department. Independent variables included causal factors (uterine atony, retained placenta, lacerations, inversion, coagulopathy, rupture, and retained tissue) and predisposing factors (age, parity, prolonged labor, birth interval, and anemia). Data analysis was performed using SPSS 26.0 with chi-square, Fisher’s exact test, and logistic regression. Results/findings: Bivariate analysis showed significant associations between PPH and birth canal tears (p = 0.011; odds ratio [OR] = 2.594) and prolonged labor (p = 0.043; OR = 0.470). Other factors, such as uterine atony, placental retention, inversion, coagulopathy, age, parity, birth spacing, and anemia, were not significant. Multivariate analysis identified birth canal tear as the most dominant factor (p = 0.003; OR = 3.766; 95% CI: 1.558–9.102), emphasizing the need for better trauma prevention and labor management. Conclusions: Limitations include the cross-sectional design, which restricts causal interpretation, and the use of secondary data from a single hospital, which potentially affects accuracy and generalizability. Contribution: This study contributes to maternal health research by identifying the key risk factors for PPH. The findings can guide clinical practices, inform preventive strategies, and serve as a reference for future research on maternal morbidity and mortality.